Solving the fokker-planck equation for some potentials using the Asymptotic Iteration Method - Alfonso, Ruby Agnes Bas; Esguerra, Jose Perico (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
We use the asymptotic iteration method to analyze the one-variable Fokker-Planck Equation. The eigenvalue and the eigenfunctions of the Fokker-Planck potential family of the form VFP (X) = -Aln (x) + X2, A ≥ 2 are obtained as well as known solutions of the parabolic and inverse parabolic potentials. In addition, equivalent Fokker-Planck potentials are obtained for Schrodinger potentials of the form Vs=Cx2k,(k=1,2,3...).
Thesis (Master of Science in Physics)--University of the Philippines Diliman
Keywords: Fokker-Planck equations -- Asymptotic theory